2009
DOI: 10.1101/lm.1190809
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced generalization of auditory conditioned fear in juvenile mice

Abstract: Increased emotionality is a characteristic of human adolescence, but its animal models are limited. Here we report that generalization of auditory conditioned fear between a conditional stimulus (CS+) and a novel auditory stimulus is stronger in 4-5-wk-old mice (juveniles) than in their 9-10-wk-old counterparts (adults), whereas nonassociative sensitization induced by foot shock (US) and the ability to discriminate CS+ from an explicitly unpaired stimulus (CSÀ) are not dependent on age. These results suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…When the BDNF +/2 mice are 3 mo of age or above, a learning deficit in fear learning occurs. In several recent studies it has been shown that fear learning differs between adolescent and adult mice, with 4-wk-old mice expressing more conditioned freezing and showing more generalized fear than 2-mo-old animals (Hefner and Holmes 2007;Ito et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…When the BDNF +/2 mice are 3 mo of age or above, a learning deficit in fear learning occurs. In several recent studies it has been shown that fear learning differs between adolescent and adult mice, with 4-wk-old mice expressing more conditioned freezing and showing more generalized fear than 2-mo-old animals (Hefner and Holmes 2007;Ito et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that overtraining protocols of fear learning also lead to a generalization of the fear response, where a defensive response is elicited even in environmental context or during exposure to cues distinct to the conditioning setting (Laxmi et al, 2003). Interestingly, enhanced generalization of fear conditioning has been observed in juvenile mice as compared with adult mice (Ito et al, 2009). This generalization, however, was significantly reduced in the presence of the explicitly unpaired cue (ie, the safety signal) in both juvenile and adult animals, suggesting that the neurobiological mechanisms required for safety learning are already functional during the adolescent period and have adaptive relevance for overcoming augmented juvenile fear generalization (Ito et al, 2009).…”
Section: Neural Correlates Of Learned Safetymentioning
confidence: 99%
“…Interestingly, enhanced generalization of fear conditioning has been observed in juvenile mice as compared with adult mice (Ito et al, 2009). This generalization, however, was significantly reduced in the presence of the explicitly unpaired cue (ie, the safety signal) in both juvenile and adult animals, suggesting that the neurobiological mechanisms required for safety learning are already functional during the adolescent period and have adaptive relevance for overcoming augmented juvenile fear generalization (Ito et al, 2009). In light of these findings, it would be tempting to explore whether, because of this heightened emotionality in adolescent animals, an Neural correlates of learned safety E Kong et al intense fear conditioning procedure could also lead to an induction of immobility in the forced-swim test.…”
Section: Neural Correlates Of Learned Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Individual components of the fear response are thought to incorporate sequentially as animals mature, eventually giving rise to what are identified as mature fear behaviors (Wiedenmayer, 2009). Indeed, several studies have revealed that distinct fear behaviors emerge at different times during early postnatal life and continue to mature during late postnatal development (Blozovski and Cudennec, 1980;Bronstein and Hirsch, 1976;Chen et al, 2006;Collier et al, 1979;Foster and Burman, 2010;Hefner and Holmes, 2007;Hubbard et al, 2004;Ito et al, 2009;Kim and Richardson, 2007;Moriceau et al, 2004;Raineki et al, 2010;Rudy, 1993;Takahashi, 1992;Wiedenmayer andBarr, 1998, 2001a,b).…”
Section: Introductionmentioning
confidence: 99%